Zbynek Zbyslav Stransky's Museological Impact on Spain (Global Journal of Human-Social Science, 2021)
Analyzing the trajectory of Z. Z. Stránský's museological thinking and his commitment to the scientific character of museology allows us to assess the importance of his museological legacy. 1 It is not surprising that his contributions have served as a point of reference for many museologists worldwide. The direct contact Stránský had with Spanish museologists, established through the debates held at ICOFOM and the ISSOM courses, makes it important to consider his influence on Spanish museology. Moreover, the study of the philosophical-scientific context, which is the basis of the entire concept of metamuseology, has served as a stimulus for Spanish museologists to direct their research work towards new museological currents. Indeed, they have done so in the conviction that they are providing a way of conceiving museology that is more in line with the needs of contemporary museums.
Keywords: z z stránský; museological theory; scientific discipline; spanish museologists; museological education